Utilization of Palm Oil Fiber (POF) as Thermal Insulated Roof Ceiling Panel - Mohd Diah, Muhamad Fazli; AHMAD JENI, MOHAMAD LUTHFI (Progress in Engineering Application and Technology, 2022)
Climate change is a major concern in the twenty-first century. In other words, this resulted in increased of energy usage on household cooling appliances. The Malaysian government's enforcement of Movement Control Orders (MCO) during the worldwide pandemic exacerbated the issue, with household energy usage increasing by about 50%. The use of thermal insulated panels is an excellent solution to this problem. However, commercial thermal insulated panels are too expensive for the majority of Malaysians, particularly those in the B40 group. Palm Oil Fiber (POF) will be employed in the construction of a thermally insulated roof ceiling panel in this study. The initial objective is to investigate the mechanical properties of POF as an insulated material for thermal insulated roof ceiling panel. This study also to determine the optimum content of POF to be used as thermal insulated ceiling panel which was a second objective in this study. To produce the ceiling panel, three samples with varying amounts of POF were combined with gypsum powder. Each sample contains a different percentage of POF, ranging from 10% to 15% to 20%. The thermal conductivity of the panel was determined for each sample using the Guarded Hot Plate test. Water absorption is the last test for the ceiling panel. This test will determine the amount of water absorbed by the panel after a short and extended duration of immersion in water. All tests were carried out in accordance with ASTM C 177, ASTM C 473, and ASTM D 1037.